An ICT-based traceability system in compound feed industry - Cebeci, Zeynel; Erdogan, Yoldas; Alemdar, Tuna; Celik, Ladine; Boga, Mustafa; Uzun, Yusuf; Coban, H. Durdu; Görgülü, Murat; Tösten, Funda (Applied Studies in Agribusiness and Commerce, 2009)
The term traceability refers to recording of flow of products along the food chain from production to consumption with inclusion of all intermediate applications involved in processing/packaging stages. The aim for establishing traceability in the food chain is to provide the timely identification and recall of batches of product from the market when a risk threatens the health of consumers. Since compound feed products are basic inputs in livestock and poultry production, ICT-based feed traceability systems can be considered as a initial step in food traceability management. These systems are simply information recording systems that are designed to trace and track the flow and characteristics of animal feed along the feed supply chain. This paper describes the architecture and some functional properties of a feed traceability system called as the “feed TRace”, focusing particularly on compound feed and integrated poultry meat industries. The feedTRace aims to improve compound feed supply chain management, to increase feed safety and quality control, and to gain marketing competencies with traceable products in compound feed industry. The system is currently under beta stage, and is tested in two high capacity feed milling plants and an integrated broiler company located inAdana province of Turkey.